An Econometric Analysis of Influence of Livestock Production on Greenhouse Gas Emission in South Africa - Megbowon, Ebenezer Toyin; Hosu, Yiseyon Sunday; Aderoju, Samuel; Nde, Samuel Che (International Journal of Energy Economics and Policy, 2025)
The aim of this article is to analyse the long-term impact of different livestock production and on greenhouse gas emissions in South Africa. Using data for the period 1981-2022, the study applied the ARDL techniques to determine the cointegration relationships and the long-run effect of the variables of interest in four models on the GHG emission. The empirical findings reveal that beef and buffalo meat production significantly reduce CH4 emissions but increase N2O emission, poultry meat production significantly reduces CO2 emission but significantly increase methane and nitrogen oxide emissions, pig meat production was found to reduce methane and nitrogen oxide emission by 0.11% and 0.98%, respectively, but have increasing effect of 0.29% on CO2. The finding obtained shows mixed results of impact of different livestock production on GHGs emission that in the long-run in South Africa. These mixed results underscore the complexity of achieving sustainable livestock production. Similarly, the variability in the impact of different types of meat production on GHG emissions indicates that a one-size-fits-all approach to mitigating emissions in the livestock sector may not be effective.